2012
DOI: 10.1063/1.4731345
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures of AlMoOy− (y = 1–4) determined by photoelectron spectroscopy and density functional theory calculations

Abstract: Vibrationally-resolved photoelectron spectra of AlMoO(y)(-) (y = 1-4) are presented and analyzed in conjunction with density functional theory computational results. The structures determined for the AlMoO(y) anion and neutral clusters suggest ionic bonding between Al(+) and a MoO(y)(-) or MoO(y)(-2) moiety, and point to the relative stability of Mo=O versus Al=O bonds. The highest occupied and partially occupied orbitals in the anions and neutrals can be described as Mo atomic-like orbitals, so while the Mo i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Since the discovery of the remarkable catalytic activity of supported gold nanoparticles for low-temperature CO oxidation, intensive studies have been carried out to elucidate the mechanisms of gold catalysts. , Even though earlier studies have suggested quantum-size effects may play a key role in gold catalysts, increasing studies have shown that the cluster–oxide support interface is also critical. Size-selected gold clusters have been extensively studied to provide insight into the nature of the catalytic effects of nanogold. Recently, tertiary clusters of Au atoms with Ti x O y clusters have been produced and their reactivity with CO has been studied as possible models to probe the support effects on the reactivity of gold. , Alumina is also an important support for gold catalysts. Aluminum oxide clusters have been investigated previously as models for oxide catalysts. More recent studies have included transition metal-doped aluminum oxides and their chemical reactivities. , But there have been no reports on Au-doped aluminum oxide clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of the remarkable catalytic activity of supported gold nanoparticles for low-temperature CO oxidation, intensive studies have been carried out to elucidate the mechanisms of gold catalysts. , Even though earlier studies have suggested quantum-size effects may play a key role in gold catalysts, increasing studies have shown that the cluster–oxide support interface is also critical. Size-selected gold clusters have been extensively studied to provide insight into the nature of the catalytic effects of nanogold. Recently, tertiary clusters of Au atoms with Ti x O y clusters have been produced and their reactivity with CO has been studied as possible models to probe the support effects on the reactivity of gold. , Alumina is also an important support for gold catalysts. Aluminum oxide clusters have been investigated previously as models for oxide catalysts. More recent studies have included transition metal-doped aluminum oxides and their chemical reactivities. , But there have been no reports on Au-doped aluminum oxide clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has conducted numerous studies on the electronic structures of transition metal oxides using anion PE spectroscopy, in addition to cluster anion reactivity studies. In general, we observed an increase in cluster EA with oxidation state, which is readily rationalized as the increased energy cost of removing an electron from an increasingly cationic M (2 y –1)/ x + center within an ionic M x O y – system as y is increased. In reactions with water, we have found two main modes of reactivity.…”
Section: Recent Advances In the Study Of Lanthanide Oxide Cluster Ani...mentioning
confidence: 81%
“…Figure shows PE spectra of Al 2 MoO 2 – , Al 2 MoO 3 – , and Al 2 MoO 4 – along with previously analyzed and published spectra of AlMoO y – ( y = 2–4) and MoO y – ( y = 2 and 3), , for direct comparison. The PE spectrum of MoO 4 – was previously measured by Wang and co-workers, and the ADE/VDE values for the lowest energy transition are included in Figure for comparison.…”
Section: Results and Analysismentioning
confidence: 97%
“…We recently reported the results of an anion photoelectron (PE) spectroscopy and density functional theory (DFT) study of several aluminum metallates [Al(TM)O y – ; TM = Mo, W], , as well as a mass spectrometric study on both anion and cation cluster distributions produced by laser ablation of TM–Al composites . The results of the PE spectroscopic studies pointed to ionic bonding between an Al + atomic cation and a (TM)O y –2 dianionic metalate for the y = 2–4 range, and the doubly occupied 3s orbital localized on the Al center being energetically within what would correlate to the TM oxide band gap.…”
Section: Introductionmentioning
confidence: 99%